Stress and burden among caregivers of persons with bipolar affective disorder during the COVID-19 pandemic in India - P D Sandya; Kannappa V Shetty; Jithin Jaise; Sanjeev Kumar Manikappa; Nagesh Brahmavar Pai (Wolters Kluwer Medknow Publications, 2022)
Introduction: Bipolar affective disorder (BPAD) is a severe mental illness causing significant problems in the lives of individuals with the disorder and those who care for them as well are. Most of the time people with mental illness are taken care of by mental health professionals, while little priority is given to their caregivers. There are numerous studies in India attempting to understand the impact of illness on caregivers and the problems faced by the caregivers of persons with BPAD. Methods: The study aimed to assess the family caregivers' stress and burden among caregivers of persons with BPAD at a tertiary care center in Dharwad, India. Descriptive research design and simple random sampling was used for recruiting 50 samples. Apart from sociodemographic schedule, burden assessment scale and perceived stress scale (PSS) were used for data collection. Results: The mean age of caregivers was 44.76 years. The average duration of illness of the patients was 9.80 years and their mean annual income was 35,500 rupees reported in the study. The mean score of impact of wellbeing subscale was higher (11.34) when compared with other sub scales of the burden assessment scale, and the overall score of burden assessment scale (31.82) indicated high levels of burden. PSS mean was 21.44, indicating high stress levels. Conclusion: The study concludes that burden and perceived stress were elevated among the caregivers of people with BPAD during the COVID-19 pandemic.